Chemical Stability of α‐Tocopherol in Colloidal Lipid Particles with Various Morphologies. Issue 6 (4th May 2020) - Schröder, Anja; Sprakel, Joris; Schroën, Karin; Berton‐Carabin, Claire C.
Abstract: Colloidal lipid particles (CLPs) are promising encapsulation systems for lipophilic bioactives, such as oil‐soluble antioxidants that are applied in food and pharmaceutical formulations. Currently, there is no clear consensus regarding the relation between particle structure and the chemical stability of such bioactives. Using α‐tocopherol as a model antioxidant, it is shown that emulsifier type (Tween 20 or 40, or sodium caseinate) and lipid composition (tripalmitin, tricaprylin, or combinations thereof) modulated particle morphology and antioxidant stability. The emulsifier affects particle shape, with the polysorbates facilitating tripalmitin crystallization into highly ordered lath‐like particles, and sodium caseinate resulting in less ordered spherical particles. The fastest degradation of α‐tocopherol is observed in tripalmitin‐based CLPs, which may be attributed to its expulsion to the particle surface induced by lipid crystallization. This effect is stronger in CLPs stabilized by Tween 40, which may act as a template for crystallization. This work not only shows how the architecture of CLPs can be controlled through the type of lipid and emulsifier used, but also gives evidence that lipid crystallization does not necessarily protect entrapped lipophilic bioactives, which is an important clue for encapsulation system design. Practical Applications : Interest in enriching food and pharmaceutical products with lipophilic bioactives such as antioxidants through encapsulation in lipid particles is growing rapidly. This research suggests that for efficient encapsulation, the particle architecture plays an important role; to tailor this, the contribution of both the lipid carrier and the emulsifier needs to be considered. Abstract : Emulsufier type and lipid composition modulate the morphology of colloidal lipid particles, which consequently affects the chemical stability of encapsulated α‐tocopherol.